2007
DOI: 10.1117/12.700235
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser ablation for volume fabrication of micro-optical arrays on large-area substrates

Abstract: Laser micromachining by ablation is an established technique for the production of 2.5D and 3D features in a wide variety of materials. Mask projection techniques using excimer lasers have been used to fabricate microstructures on large panels where diamond turning and reflow techniques have reached their limits. We have developed 3D structuring tools based upon UV laser ablation of polymers to create large arrays of repeating micro-optical features. Synchronization of laser pulses with workpiece movement allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In particular, UVlaser ablated polymer accompanied by a surface modification is an interest field in micro-electromechanical systems 3 and micro opto-electro mechanical systems. 4 The microscopical observations on laser-ablated surface polymer have shown that micro conical structures can be formed. Experimental and theoretical investigations of these micro conical structures and laser ablated polymer have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, UVlaser ablated polymer accompanied by a surface modification is an interest field in micro-electromechanical systems 3 and micro opto-electro mechanical systems. 4 The microscopical observations on laser-ablated surface polymer have shown that micro conical structures can be formed. Experimental and theoretical investigations of these micro conical structures and laser ablated polymer have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the metal tracks for bonding and probing the VCSEL were defined on top of the SU8 layer by using image reversal lithography, evaporating a Ti/Ni/Au stack (20 nm/50 nm/300 nm) and doing lift-off. After metal tracks definition, the SU8 prisms with an angle of 24° were fabricated on top of the GCs using non-uniform laser ablation [14]. The optimum value for the prism angle was calculated to be 24° using Snell's law for a normal incidence on prism face such that it resulted into a 10° incidence angle onto the GCs.…”
Section: Flip-chip Bonding Of Vcsel To Soimentioning
confidence: 99%
“…Great advances have been made in the technological applications of UV laser polymer ablation since this was first reported in 1982. 1 It has become possible to fabricate a variety of microstructures with complex surface relief for use in microelectromechanical systems ͑MEMS͒, 2 microoptoelectromechanical systems ͑MOEMS͒, 3 lab-on-chip, 4 as well as surfaces with special physical properties. 5 Whether variable surface height is machined by changing aperture shape, synchronized-image-scanning, mask/workpiece dragging, or half-tone masks, 2 the shaping demanded often means the surface presented for ablation lies well off normal incidence.…”
mentioning
confidence: 99%